MARKET REACTION TO EARNINGS MANAGEMENT AND THE ROLE OF AUDIT QUALITY: EVIDENCE FROM INDONESIA - Ratnaningrum Ratnaningrum; Indrian Supheni; Risma Nurhapsari (SEAN Institute, 2023)
This study aims to determine whether the earnings management influences market reaction and whether audit quality moderates the relationship between earnings management and market reactions. The research sample has 115 manufacturing companies that go public in Indonesia Stock Exchange listed in 2013 – 2015 so that the number of samples (n) = 345 observations. Discretionary accruals are used to gauge the earnings management.. This study uses boostrap test to examine the hypothesis. The result shows that earnings management affects the market reaction positively. So it indicates if the market still gives a positive reaction to the report that generates earnings even though it contains earnings management. The interaction between book value equity and audit quality has a significant positive effect on the relationship between earnings management and market reaction.